The polychromatic retrigger: a new tool to mitigate pileup in spectral photon-counting computed-tomography - Amato, Carlo; Disch, Christian; Zambon, Pietro (Frontiers in Physics, 2024)
High photon rates, like the ones required in clinical computed tomography, can generate pulse pileup in photon-counting detectors, and in extreme cases induce system paralysis. The instant retrigger technology has been developed by DECTRIS Ltd. to counteract such phenomena, effectively making detectors non-paralyzable. The instant retrigger behavior is regulated by a quantity named retrigger time, which originally was the same for all the energy thresholds of the detector. We developed a new ASIC that features an improved version of the instant retrigger (polychromatic retrigger) that allows different retrigger times for each of the four energy thresholds.In this work, we investigate how this feature can be exploited in computed tomography to mitigate pileup artifacts. Using a Monte Carlo method, we modeled a full computed tomography system with four energy thresholds (20 , 50 , 70 and 90 keV), and we simulated head scans from low (1 × 10 7 cps/mm 2 ) to high (1 × 10 9 cps/mm 2 ) photon count rates for different values of the retrigger time. The quality of the resulting images generally degrades when increasing the photon rates (pileup artifacts) and, at the same time, it becomes strongly dependent on the retrigger time.We show how, even at high incoming rates, it is possible to identify for each energy threshold a retrigger time value that restores almost completely the image quality obtained in the low count-rate scenario. The analysis indicates that the higher the energy threshold, the longer the retrigger time has to be set.